The Relationship between Severity of Hearing Loss and Subjective Tinnitus Loudness among Patients Seen in a Specialist Tinnitus and Hyperacusis Therapy Clinic in UK - Aazh, Hashir; Salvi, Richard (Journal of the American Academy of Audiology, 2019)
Hearing loss is often associated with the phantom sound of tinnitus. However, the degree of the association between severity of hearing loss and tinnitus loudness taking into account the impact of other variables (e.g., emotional disturbances) is not fully understood. This is an important question for audiologists who are specialized in tinnitus rehabilitation as patients often ask whether the loudness of their tinnitus will increase if their hearing gets worse.To explore the relationship between tinnitus loudness and pure tone hearing thresholds.This was a retrospective cross-sectional study.445 consecutive patients who attended a Tinnitus and Hyperacusis Therapy Specialist Clinic in UK were included.The results of audiological tests and self-report questionnaires were gathered retrospectively from the records of the patients. Multiple-regression analysis was used to assess the relationship between tinnitus loudness, hearing loss and other variables.The regression model showed a significant relationship between the pure tone average (PTA) at the frequencies 0.25, 0.5, 1, 2, and 4 kHz of the better ear and the tinnitus loudness as measured via visual analogue scale (VAS), r (regression coefficient) = 0.022 (p < 0.001). Other variables significantly associated with tinnitus loudness were tinnitus annoyance (r = 0.49, p < 0.001) and the effect of tinnitus on life (r = 0.09, p = 0.006). The regression model explained 52% of the variance of tinnitus loudness.Although increased tinnitus loudness was associated with worse PTA, the relationship was very weak. Tinnitus annoyance and impact of tinnitus on life were more strongly correlated with tinnitus loudness than PTA.
Keywords: hyperacusis; psychological assessment; pure-tone hearing thresholds; tinnitus loudness; uncomfortable loudness levels